Isolation of food-borne pathogen bacteriophages from retail food and environmental sewage - Thung, Tze Young; Mohd Fadzil, Siti Norshafawatie; Premarathne, Jayasekara Mudiyanselage Krishanthi Jayarukshi Kumari; Chang, Wei San; Loo, Yuet Ying; Kuan, Chee Hao; New, Chia Yeung; Anyi, Ubong; Bahumaish, Ramzi Othman Saeed; Mahyudin, Nor Ainy; Basri, Dayang Fredalina; Wan Mohamed Radzi, Che Wan Jasimah; et al. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Bacteriophages are the viruses of bacteria and are widely distributed in the biosphere, exhibiting dramatic manifestations both in liquid cultures and on solid media. In this study, bacteriophages were isolated from different types of food (beef, chicken meats, cucumber, lettuce, clam, cockles and shrimp) and sewage samples using 6 reference pathogen strains (Salmonella Enteritidis, Salmonella Typhimurium, Campylobacter jejuni, Vibrio parahaemolyticus, Listeria monocytogenes and Escherichia coli). A total of 29 bacteriophage isolates were obtained and further examined for titer via agar overlay assay. The titers were determined within the range of 108 to 1011 PFU/mL. Our results showed that diverse of bacteriophages are naturally present in a variety of foods.